2015
DOI: 10.1111/mms.12263
|View full text |Cite
|
Sign up to set email alerts
|

Southern right whale (Eubalaena australis) calf mortality at Península Valdés, Argentina: Are harmful algal blooms to blame?

Abstract: Península Valdés (PV) in Argentina is an important calving ground for southern right whales (SRWs, Eubalaena australis). Since 2005, right whale mortality has increased at PV, with most of the deaths (~90%) being calves <3 mo old. We investigated the potential involvement of harmful algal blooms (HABs) in these deaths by examining data that include: timing of the SRW deaths, biotoxins in samples from dead SRWs, abundances of the diatom, Pseudo‐nitzschia spp., and the dinoflagellate, Alexandrium tamarense, shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 50 publications
0
27
0
2
Order By: Relevance
“…Similarly, DA has been frequently detected in phytoplankton samples from different zones of the Argentine Sea in the last few years (Negri et al, 2004;Sastre et al, 2007;Cadaillón, 2012;Krock et al, 2015). Indeed, Pseudo-nitzschia blooms have been suggested as potentially responsible for calf mortalities of southern right whales along the Valdés Península Wilson et al, 2015). During these episodes, DA production was mainly associated with elevated cell densities of P. australis (Negri et al, 2004) or P. fraudulenta (Cleve) Hasle (Sastre et al, 2007), but the co-occurrence of several other Pseudonitzschia species (Cadaillón, 2012;Krock et al, 2015), makes it difficult to unequivocally identify the responsible taxa.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, DA has been frequently detected in phytoplankton samples from different zones of the Argentine Sea in the last few years (Negri et al, 2004;Sastre et al, 2007;Cadaillón, 2012;Krock et al, 2015). Indeed, Pseudo-nitzschia blooms have been suggested as potentially responsible for calf mortalities of southern right whales along the Valdés Península Wilson et al, 2015). During these episodes, DA production was mainly associated with elevated cell densities of P. australis (Negri et al, 2004) or P. fraudulenta (Cleve) Hasle (Sastre et al, 2007), but the co-occurrence of several other Pseudonitzschia species (Cadaillón, 2012;Krock et al, 2015), makes it difficult to unequivocally identify the responsible taxa.…”
Section: Introductionmentioning
confidence: 94%
“…Península Valdés is a significant source of bivalve mollusks for human consumption in Argentina, and algal toxins and harmful algal blooms (HABs) have been monitored in PV since 1985 (Wilson et al 2015). In general, elevated HAB species and associated biotoxins such as saxitoxin and domoic acid have not been linked to significant human or animal morbidity or mortality at PV, though biotoxin-or HAB-related human and seabird deaths have periodically occurred (Wilson et al 2015).…”
Section: Chemical Pollutants and Algal Toxinsmentioning
confidence: 99%
“…In general, elevated HAB species and associated biotoxins such as saxitoxin and domoic acid have not been linked to significant human or animal morbidity or mortality at PV, though biotoxin-or HAB-related human and seabird deaths have periodically occurred (Wilson et al 2015). In 2 previous studies, low levels of saxitoxin or domoic acid were detected in tissues from dead whales (Wilson et al 2015), and frustules of potentially toxic Pseudo-nitzschia were identified in feces of living and dead PV SRWs (D'Agostino et al 2015). However, spatial or temporal relationships between algal biotoxin production and whale mortality peaks were not found.…”
Section: Chemical Pollutants and Algal Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Runchie and Muhling (both class of 2017) used satellite data to describe the habitat preferences of bluefin tuna in the California Current [32]. Post-course collaboration between course instructors and participants has resulted in the development of habitat models [33,34], and the use of satellite chlorophyll measurements to assess the potential influence of harmful algal blooms on the decade-long increase in Southern Right Whale mortality [35].…”
Section: Operational Outcomesmentioning
confidence: 99%